ANALISIS MANAJEMEN RISIKO DI UNIT SIRKULASI PERPUSTAKAAN FAKULTAS X - Ratih Surtikanti (Program Pendidikan Vokasi Universitas Indonesia, 2015)
AbstractThe role of records management is often only realized by an organization or a person whenthere are problems or difficulties that can only be overcome if there is a document that contains thenecessary information. analysis of effective record management so organizations can reorganize theexisting record management system in accordance with the most important priority for theorganization. With the improvement in the organization's records management system is expectedin the foreseeable future will not encounter any problems either in the fields of law, finance, as wellas the administrative history.Keywords:. Record management, risk management, library governance